2018
DOI: 10.1021/acsami.8b19302
|View full text |Cite
|
Sign up to set email alerts
|

Ambient-Pressure X-ray Photoelectron Spectroscopy Characterization of Radiation-Induced Chemistries of Organotin Clusters

Abstract: Advances in extreme ultraviolet (EUV) photolithography require the development of next-generation resists that allow high-volume nanomanufacturing with a single nanometer patterning resolution. Organotin-based photoresists have demonstrated nanopatterning with high resolution, high sensitivity, and low-line edge roughness. However, very little is known regarding the detailed reaction mechanisms that lead to radiation-induced solubility transitions. In this study, we investigate the interaction of soft Xray rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 53 publications
3
26
2
Order By: Relevance
“…The ESI-MS spectrum of the tin-oxo cage compound was reported earlier by Dakternieks and coworkers, 32 who observed a main peak at m/z 1218, assigned to the dication [(nBuSn) 12 -O 14 (OH) 6 ] 2+ . This result was reproduced in our experiments (see ESI, † Fig.…”
Section: Mass Spectra Of Tin-oxo Cage Ionssupporting
confidence: 54%
See 1 more Smart Citation
“…The ESI-MS spectrum of the tin-oxo cage compound was reported earlier by Dakternieks and coworkers, 32 who observed a main peak at m/z 1218, assigned to the dication [(nBuSn) 12 -O 14 (OH) 6 ] 2+ . This result was reproduced in our experiments (see ESI, † Fig.…”
Section: Mass Spectra Of Tin-oxo Cage Ionssupporting
confidence: 54%
“…To achieve sufficient photon absorption in thin films, and potentially higher etch resistance, metal-containing photoresist materials have been proposed as alternatives. [7][8][9][10][11][12][13] An example of an organometallic photoresist material is the tin-oxo cage (see Fig. 1), 14,15 first described by Puff and Reuter in 1989.…”
Section: Introductionmentioning
confidence: 99%
“…Cardineau et al [11] were the first to study tin oxo cages as EUV photoresists, and suggested that tincarbon bond cleavage is the key step in the radiation induced reactions. This model is also supported by computational [12] and experimental studies in more recent work [13][14][15]. Hinsberg and Meyers [16] proposed a numerical model describing the reaction process in metal oxide-based resists.…”
Section: Introductionmentioning
confidence: 69%
“…We use the tin density for a 20 nm thick β-NaSn 13 film, which was obtained by Rutherford back scattering, to estimate the initial butyl group coverage (θ 0 ) as ∼8.9 × 10 15 butyl groups/cm 2 . 25 Simplified equations derived from the transition-state theory 26 allow us to calculate reasonable values for ν at the desorption temperature T p = 696 K and chain length N = 4. This analysis yields ν min = 7.3 × 10 15 s −1 and ν max = 1.1 × 10 21 s −1 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%